Waffen-SS : Hitler's Army at war - Gilbert, Adrian (Da Capo Press, Hachette Book Group, Inc, 2019)
Himmler's Army -- Foundation Stones -- Creating an Elite -- The March to War -- The Destruction of Poland -- Deployment in the West -- Invading the Netherlands -- The Assault on France -- France Defeated -- Transition and Expansion -- Balkan Diversion -- The Greatest War in History -- Operation Barbarossa -- Advance on Leningrad: Army Group North -- Across the Ukraine: Army Group South -- Drive on Moscow: Army Group Center -- Holding the Line: Eastern Front -- At the Edge: Eastern Front 1942-43 -- Kharkov Counterstroke -- Kursk: Clash of Armor -- A Call to Arms -- An Army of Europeans -- Defending the Ukraine -- Battle in the North -- Shoring up the Line -- Partisan Wars: The Eastern Front -- Partisan Wars: The Balkans -- War in the West -- Battle for the Beachhead -- Unequal Struggle -- Collapse and Recovery -- Final Gamble in the West -- Fight to the Last -- Disaster in Hungary -- The Waffen-SS Destroyed -- Aftermath.